Pengaruh Fasilitas Kerja, Job Description Dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Cabang Dinas Pendidikan Siantar - Irmayanti Sinaga; Dewi Marito Sidabutar; Lena Hariani Nasution; Mesrini Bondar (Manajemen dan Bisnis, 2022)
This formula research internal issue is how influence  of  job facility on employees  job satisfaction. How influence of    job description  on employees  job satisfaction. How influence of   organization culture   on employees  job satisfaction. How influence of job facility,   job description  and    organization culture   on employees  job satisfaction. This research target is to for know influence and analyze of    job facility on employees  job satisfaction. For know influence and analyze   job description  on employees  job satisfaction. For know influence and analyze   organization culture   on employees  job satisfaction. For know influence and analyze   job facility,    job description and    organization culture on employees  job satisfaction   Sample in this research amount to 36 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of  job facility effect positive and significant on employees  job satisfaction.   Job description  effect positive and significant on employees  job satisfaction.   Organization culture   effect positive and significant on employees  job satisfaction.     Job facility,  job description  and    organization culture   effect and positive and significant on employees  job satisfaction